(untitled) (lectio difficilior, 2010)
With the 22th edition of lectio difficilior the editors, all the women on the editorial board, and the authors celebrate the tenth anniversary of a successful project. We understand the brief gathering at the International Meeting of the Society of Biblical Literature in Tartu (Estonia) as the beginning of a phase of reflection that may be significant not only for the project of our journal but also for feminist exegesis more generally. What did we achieve in the last ten years? In what respect has the field of research changed? Are we content with our accomplishments? Or, has progress come to a standstill? What does „feminist” mean with regard to our exegesis, hermeneutics, and theology? What is the relationship between feminism and gender studies? Last but not least: how are feminist exegetes present in teaching and research? Our task is not to answer these questions, yet perhaps to contribute some long-term observations that may be important for a required potential analysis. The articles of this issue of lectio difficilior focus on such observations.